The Collaborative Redesign of ‘Authentic’ Technology-Enhanced Learning: Analysis of a Change Laboratory Research-Intervention in Engineering Higher Education - Philip Moffitt; Brett Bligh (Trends in Higher Education)
This paper contributes to international debates about ‘authenticity’ in higher education, especially where this is embroiled in technology-oriented aspects of educational policy and practice. It describes activity theoretical research in a setting of engineering higher education, in industrial attachments taking place at distance, during which students and lecturers experience problems with technology-mediated interactions. Prior to the research-intervention that we describe in the paper, these interactions had been implemented through top-down policy, with work-related practices being conducted in the name of authenticity—a notion used in framing education as preparing students for economic work, in which digital technologies are increasingly embroiled. We describe an activity theoretical approach, and an online Change Laboratory methodology, through which students and lecturers envision and enact change to these practices. Their activity is thus reconfigured through their confrontation and renegotiation of authenticity. Our core contribution is to illustrate, through exposing and aggravating contradictions in technology-mediated activity, how practice in higher education can be considered authentic in and of itself, as distinct from solely having authenticity in preparing students for economic work.